2003
DOI: 10.1002/abio.200390025
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Polyaromatic Hydrocarbons (PAHs) through Landfarming with Biostimulation and Bioaugmentation

Abstract: Many soils contaminated with high molecular weight hydrocarbons (HMW PAHs) contain PAHdegrading microorganisms. These microbes are often limited in their degradation capability because of some limiting environmental factors (i.e., low aqueous solubility of PAHs, low bioavailability of PAHs, nitrogen or other nutrient limitation, high co-contamination levels such as pentachlorophenol [PCP] that can inhibit PAH biodegradation, etc.). Microcosm studies were done using biostimulation (addition of ground rice hulls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 30 publications
0
60
0
7
Order By: Relevance
“…Treatment strategies vary for landfarms and can be tailored according to site-specific characteristics including climate, location, soil type and temperature (Paudyn et al 2008). Nutrient amendments, pH buffers and bulking agents may be applied to stimulate aeration of co-substrates, microbial metabolism or bacterial inoculations and can significantly increase remediation efficiency (Straube et al 2003;Paudyn et al 2008;Filler et al 2009). The success of landfarming in temperate environments is well reported (McCarthy et al 2004); however, landfarming trials in cold regions are comparatively scarce and field trials from the Antarctic and Arctic have revealed conflicting results (Delille 2000;Aislabie et al 2004;McCarthy et al 2004;Paudyn et al 2008;Chang et al 2010).…”
Section: Landfarmingmentioning
confidence: 99%
“…Treatment strategies vary for landfarms and can be tailored according to site-specific characteristics including climate, location, soil type and temperature (Paudyn et al 2008). Nutrient amendments, pH buffers and bulking agents may be applied to stimulate aeration of co-substrates, microbial metabolism or bacterial inoculations and can significantly increase remediation efficiency (Straube et al 2003;Paudyn et al 2008;Filler et al 2009). The success of landfarming in temperate environments is well reported (McCarthy et al 2004); however, landfarming trials in cold regions are comparatively scarce and field trials from the Antarctic and Arctic have revealed conflicting results (Delille 2000;Aislabie et al 2004;McCarthy et al 2004;Paudyn et al 2008;Chang et al 2010).…”
Section: Landfarmingmentioning
confidence: 99%
“…It is known that many soils contaminated with PAHs contain PAH-degrading microorganisms. These microbes are often limited in their degradation capacity because of some limiting environmental factors such as aqueous solubility of PAHs, low bioavailability of PAHs, nitrogen or other nutrient limitation, high co-contamination levels that can inhibit PAH biodegradation (Straube et al 2003). This fact could be a partial explanation why PAHs degraded well in the soil Polluted-PAH and partly also in the soil Control-PAH, whereas no decrease was found in the sewage sludges amended soil Polluted-sew.sl-PAH.…”
Section: Persistent Organic Pollutantsmentioning
confidence: 99%
“…On the other hand, the microbes are often limited in their degradation capability because of some limiting environmental factors (i.e., low aqueous solubility of PAHs, low bioavailability of PAHs, nitrogen or other nutrient limitation, high cocontamination levels such as pentachlorophenol (PCP) that can inhibit PAH biodegradation, etc.) (Straube et al 2003).…”
mentioning
confidence: 99%
“…DS10-129, increased the bioremediation process in an oilcontaminated soil (Rahman et al 2002). Similarly, Straube et al (2003) reported that adding P. aeruginosa strain 64 enhanced the bioremediation in a soil contaminated with PAHs and pentachlorophenol. Kumar et al (2008) reported that a crude biosurfactant from the Pseudomonas DHT2 strain isolated from an oil-contaminated soil enhanced the solubility of PAHs in a dosedependent manner.…”
Section: Applications Of Rhamnolipidsmentioning
confidence: 87%